Varicella Zoster Virus Vasculopathy - Nagel, Maria A (J Infect Dis, 2018)
Varicella zoster virus (VZV) is a ubiquitous, exclusively human alphaherpesvirus that produces varicella then becomes latent in ganglionic neurons. In elderly and immunocompromised individuals, VZV reactivates and typically produces herpes zoster. Studies of patients with VZV vasculopathy have identified key clinical, imaging, and laboratory features to assist in diagnosis and treatment. Complementary studies have further expanded the spectrum of VZV vasculopathy to include the extracranial circulation and identified mechanisms contributing to its pathogenesis. Given our increasing aging population and recognition that VZV reactivation manifesting as zoster is a risk factor for stroke and myocardial infarction, recognition of VZV as a potential cause of vascular disease with or without associated zoster rash is essential to decrease associated morbidity and mortality because VZV vasculopathy can be treated with antiviral therapy.